KEANEKARAGAMAN JENIS DAN KONDISI TEMPAT TUMBUH KANTONG SEMAR (Nepenthes spp.) DI KAWASAN HUTAN GUNUNG SELINDUNG DESA TWI MENTIBAR KECAMATAN SELAKAU KABUPATEN SAMBAS - Gusdiarto, .; Astiani, Dwi; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2018)
There is a complex vegetation structure that creates a different living environment and has its diverse plant species, habitat of plants in tropical rain forest is one of them. This forest has its rich in terms of flora species in Indonesia, one of them is Nepenthes spp. Nepenthes spp. is a unique plant that grows in forests. Its diverse colors and forms make it as an ornamental plant with high economic value. The aim of this study is to determine the variety of Nepenthes spp. and to assure the condition of the place where it grows in natural forest. This research was conducted by using field survey method, with multiple plot. Plot placement on the field was done with purposive sampling. Based on results of the research of secondary forest it is found three types of Nepenthes spp. The species found in this secondary forest are Nepenthes mirabilis Druce, Nepenthes ampullaria Jack and Nepenthes reinwardtiana Miq. These 3 species found with each density of 318, 89 and 636 m/ha, each dominance index is <1. The micro climate ranges result on the habitat are, the air temperature: 16.67 0C - 24,67 0C, humidity: 65,33% - 70,33%, soil temperature: 250C - 26,6 0C, soil moisture: 30% - 34,33% and light intensity: 25,94 Lux- 32,94 Lux.Keywords: Diversity of nepenthes, Gunung Selindung, habitat, nepenthes.